Battery integrated three input high gain DC-DC converter for renewable energy sources - Azuka, Affam; Yonis M Yonis, Buswig; Al-Khalid, Hj Othman; Shanti Faridah, Salleh; Hazrul, Mohamad Basri; Norhuzaimin, Julai; Kasumawati, Lias (Institute of Advanced Engineering and Science (IAES), 2025)
In this work, a battery integrated three input converter is proposed. The topology combines a traditional boost converter on one side with a noncoupled inductor-based buffer stage on the other side. Some merits of the converter are a high voltage gain, high output voltage in the battery discharging mode, and a wide range of output voltage. The bidirectional port makes it attractive for renewable energy (RE) sources like solar and fuel cell. The converter can operate in three modes that are determined by the availability of RE sources and the battery state of charge (SOC). The power management algorithm enabled the converter to work in either single input, double input or three input configurations. The duty ratios of assigned power switches controlled the output voltage and the battery charge/discharge. Steady-state analyses, and the dynamic modeling are presented and discussed. At 12 V and 24 V input voltage, output voltage of 315.52 V was delivered in the battery excluded mode. The battery discharging mode delivered 311.57 V while the battery charging mode delivered 301.32 V. The proposed converter can serve low to medium power voltage/ power applications. The hardware experiments verify the workings of the proposed converter